The Use of Altman Z-Score, Springate, and Zmijewski in Detecting Financial Distress in the Transportation and Logistics Sector Companies - Tyus Krisyuanto; Gideon Setyo Budiwitjaksono (Transpublika Publisher, 2025)
This research aims to explore how the Altman model (Variable X1), the Springate model (Variable X2), and the Zmijewski model (Variable X3) affect financial distress. A quantitative approach is used, with information gathered from secondary sources, specifically financial statements of transportation and logistics firms on the Indonesia Stock Exchange. The analysis includes systematic compilation, tabulation, and examination of data. The findings from the discriminant analysis indicate that only the Springate model (X2) demonstrates statistical significance, whereas both the Altman (X1) and Zmijewski (X3) do not achieve significance. In terms of predictive accuracy for each model, Altman yields 54.16%, Springate provides 58.33%, and Zmijewski records 16.66%. In summary, within companies operating in the transportation and logistics sector, it is evident that Springate model (X2) possesses a substantial influence in forecasting instances of financial distress, while neither the Altman (X1) nor Zmijewski (X3) models exhibit a comparable level of influence. The findings indicate that the Springate model is the most effective tool for predicting financial distress in this sector.